A new genus of Protasteridae (Ophiuridea) from the Lower Devonian Bokkeveld Group of South Africa - Reid, Mhairi; Hunter, Aaron W.; Taylor, Wendy L.; Bordy, Emese M. (Evolutionary Studies Institute, 2019)
Gamiroaster tempestatis, a new genus and species of Palaeozoic ophiuroid, is described from four specimens identified in the Lower DevonianVoorstehoek Formation (Ceres Subgroup, Bokkeveld Group) of SouthAfrica. This ophiuroid belongs the family Protaseridae, a Middle–Late Ordovician taxon that continued into the late Palaeozoic. This new ophiuroid forms part of a much wider fauna of the Malvinokaffric Realm, a biogeographical termused to denote the cool- to cold-water, high-latitude endemic, benthic marine, Devonian faunas of southwestern Gondwana, which also includes the invertebrate fossil assemblages of the Argentine Precordillera and the Fox Bay Formation of the Falkland Islands. The specimens were collected from an obrution deposit excavated on Karbonaatjies farm, ~145 km northeast of Cape Town in theWestern Cape. The excavated rock samples contain >700 articulated specimens of Gamiroaster tempestatis that are closely associated with two types of less common mitrate stylophorans. Silicone casts and high-resolution three-dimensional digital models obtained via micro-CT scanning of these mould fossils provided detailed morphological proxies for this taxonomic description.
Keywords: Asterozoans; Ophiuroids; Malvinokaffric Realm; Emsian; Gamiroaster tempestatis